Active Spanwise Lift Control - Dias, Joaquim Neto (American Institute of Aeronautics & Astronautics, 2020)
Active Spanwise Lift Control presents a novel approach to tackle the gust alleviation problem. Traditional approaches typically attempt to suppress the structural response at discrete points of the wing using only the conventional control surfaces (aileron, elevator, rudder), resulting in limited control authority, high-bandwidth actuator requirements, and necessity of gust field measurements ahead of the aircraft. In this book, the authors directly address th.